Leaving Women Behind: Modern Families, Outdated Laws - Strassel, Kimberley A.; Colgan, Celeste; Goodman, John C.; Hutchison, Se n. Kay Bailey (Rowman & Littlefield Publishers, 2007)
Paternalistic federal laws and regulations thwart initiatives to grant women the same economic liberties as men. Why have federal institutions overseeing employment, employee benefits, childcare, taxation, health care, education, retirement, and social security adopted such a warped and antiquated perspective of traditional family life? And what can be done about it? Leaving Women Behind answers these important and provocative questions. The authors call upon the federal government to get out of the way of marketplace initiatives. Employers and employees across the country are perfectly capable of making mutually beneficial adjustments if the government simply unties their hands. They offer realistic solutions; solutions that involve empowering people, giving them more choices, and making government less intrusive. Published in cooperation with The Manhattan Institute and The National Center for Policy Analysis.